Coated titanium anode material and method for its production
Patent Information
- Application Number
- CN202611165747.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-08-03
AI Technical Summary
[0006]鉴于此,本发明提出了一种涂层钛阳极材料及其制备方法,用以解决现有钛基-铱钽氧化涂层阳极电催化活性与络合剂抑制能力无法兼顾的问题
1.本发明在保持整体高钽低铱的基础组成不变的同时通过锑、铈双掺杂调控涂层活性位点的电子结构与表面配位环境,在不提高铱占比、不增强界面氧化性的前提下,提升析氧反应的活性与反应选择性,同时弱化对柠檬酸络合剂的吸附与氧化。
Abstract
Description
Technical Field
[0001] This invention relates to the field of titanium anode coating preparation technology, and more specifically, to a coated titanium anode material and its preparation method. Background Technology
[0002] In citric acid electroplating systems, citric acid and its salts act as core complexing agents, playing a crucial role in regulating the concentration of free metal ions, improving the dispersion and deep plating capabilities of the plating solution, and ensuring the uniformity and overall performance of the coating. This system requires the use of insoluble anodes. Among these, titanium-based iridium-tantalum oxide coated anodes have become the mainstream alternative to stainless steel and platinum anodes due to their advantages such as no substrate dissolution contamination, stable oxygen evolution performance, and lower cost compared to pure precious metal anodes.
[0003] Patent CN121344574B discloses a titanium-based iridium-tantalum oxide-coated anode and its preparation method. This method employs a two-step coating process: first, a solution containing a tantalum source is brushed onto a titanium substrate, followed by repeated sintering at 600-620℃ to prepare a tantalum-coated titanium substrate; then, an iridium-tantalum oxide coating solution containing tantalum pentachloride, chloroiridic acid hexahydrate, and zirconium chloride is brushed onto the substrate, followed by repeated sintering to obtain the finished anode. This method controls the overall tantalum to iridium mass ratio of the coating to be 6-7:4-5, ensuring that the tantalum mass fraction is greater than 5% of the iridium mass, relying on the high proportion of inertness. It reduces the oxidizing properties of the anodic interface and inhibits the decomposition of the complexing agent in the alkaline system; at the same time, by adding zirconium chloride accounting for 2%~5% of the total molar amount of the main salt, it refines the coating grains and fills microcracks, thereby improving the coating cracking problem under high tantalum ratio.
[0004] While it alleviates the problems of rapid decomposition of complexing agents and coating cracking in citric acid systems, it still has the following issues: Electrocatalytic activity and complexing agent inhibition ability cannot be simultaneously achieved. This scheme employs an overall homogeneous high-tantalum, low-iridium composition design, while As an intrinsically inert and high-resistivity component, an increase in its proportion directly reduces the coating's conductivity and oxygen evolution catalytic activity, leading to an increase in the anodic oxygen evolution overpotential and a higher cell voltage. However, increasing the iridium proportion to enhance catalytic activity simultaneously increases the oxidative properties of the anodic interface, significantly boosting the decomposition rate of the complexing agent.
[0005] Therefore, the present invention proposes a coated titanium anode material and its preparation method, which has important practical significance. Summary of the Invention
[0006] In view of this, the present invention proposes a coated titanium anode material and its preparation method to solve the problem that the electrocatalytic activity and complexing agent inhibition ability of existing titanium-based iridium-tantalum oxide coated anodes cannot be simultaneously achieved.
[0007] This invention proposes a coated titanium anode material and its preparation method, comprising the following preparation steps: The titanium substrate was pretreated and then etched with oxalic acid to obtain the treated titanium substrate. Tantalum pentachloride, tin tetrachloride and titanium tetrachloride were added to n-butanol solution and stirred to dissolve. After ultrasonic dispersion, a transition layer coating solution was obtained. The transition layer coating liquid is applied to the surface of the treated titanium substrate and subjected to first gradient coating sintering to obtain a tantalum-tin-titanium composite oxide transition layer. A mixed solvent is obtained by mixing concentrated hydrochloric acid, n-butanol and isopropanol. Tantalum pentachloride, chloroiridium hexahydrate, antimony trichloride, cerium nitrate hexahydrate and iridium tantalum oxide nanocrystal seed crystals are added to the mixed solvent and dispersed by ultrasonication to obtain an active coating liquid. After the active layer coating solution is applied to the surface of the tantalum-tin-titanium composite oxide transition layer, it is subjected to negative pressure degassing treatment. After treatment, a second gradient coating sintering is performed. After post-treatment, the coated titanium anode material is obtained.
[0008] Furthermore, the preprocessing specifically includes: After removing the surface oxide scale by sanding the titanium substrate with 800-grit sandpaper, rinse with deionized water, and then sand with 80-120-grit quartz sand at 3-4 kg / m². The titanium substrate was roughened by sandblasting at a certain pressure to control the surface roughness Ra = 3~5μm. The titanium substrate was then placed in a solution of NaOH with a concentration of 40g / L. Concentration of 40g / L The mixture was kept at 75°C for 25 minutes in a 40 g / L alkaline solution, then removed and washed with deionized water until neutral.
[0009] Furthermore, the oxalic acid etching specifically involves immersing the treated titanium substrate in a 12% (w / w) oxalic acid solution, hot-soaking it at 105°C for 1.5 hours, rinsing it with deionized water until neutral, and then drying it at 105°C.
[0010] Furthermore, the first gradient coating sintering specifically involves: The transition layer coating solution was brushed onto the treated titanium substrate surface at a coating volume of 0.9 mL / m³. Then, gradient sintering is performed. First, the temperature is increased to 220°C at a rate of 3°C / min and held for 10 min. Then, the temperature is increased to 360°C at a rate of 3°C / min and held for 15 min. Then, the temperature is increased to 510°C at a rate of 2°C / min and held for 25 min. After the process, the temperature is reduced to 200°C in the furnace and then removed and air-cooled to room temperature. The brushing and gradient sintering steps are repeated 3 to 4 times. When performing the last gradient sintering, the holding time at 510°C is extended to 45 min.
[0011] Furthermore, when tantalum pentachloride, iridium chlorohydrate, antimony trichloride, cerium nitrate hexahydrate, and iridium tantalum oxide nanocrystal seed crystals are added to the mixed solvent: Weigh out tantalum pentachloride and chloroiridium hexahydrate according to the mass ratio of tantalum to iridium = 6.5:3.5; The total molar amount of antimony trichloride and cerium nitrate hexahydrate is 4% of the total molar amount of tantalum pentachloride and chloroiridium hexahydrate, wherein the molar ratio of antimony trichloride and cerium nitrate hexahydrate is 6:4; The mass of the iridium-tantalum oxide nanocrystal seed crystal is 2% of the total mass of tantalum and iridium elements.
[0012] Furthermore, the preparation method of the iridium-tantalum oxide nanocrystal seed crystal is as follows: Tantalum pentachloride and chloroiridium hexahydrate were weighed according to a molar ratio of 1:1 for tantalum and iridium. The tantalum pentachloride was added to concentrated hydrochloric acid with a mass fraction of 37% under ice bath stirring until dissolved, resulting in a mixed solution with a tantalum ion concentration of 0.2 mol / L. The chloroiridium hexahydrate was added to the mixed solution and stirring was continued until dissolved, resulting in a tantalum-iridium mixed metal salt mother liquor. Anhydrous ethanol was added to the mother liquor of the tantalum-iridium mixed metal salt to adjust the total metal ion concentration in the system to 0.1 mol / L. Then, citric acid monohydrate was added to the system at a molar ratio of citric acid monohydrate to total metal ions = 1.2:1 and stirred until completely dissolved to obtain the first mixed solution. The first mixed solution was placed in a water bath at 40°C, and 10% ammonia solution was added dropwise with stirring to adjust the pH of the system to between 3.0 and 3.5. After the addition was completed, the mixture was kept warm and stirred for 30 minutes to obtain an iridium-tantalum composite sol. The iridium-tantalum composite sol was aged in a water bath at 60°C for 12 hours to obtain a wet gel. The wet gel was dried at 105°C for 6 hours to obtain an iridium-tantalum dry gel precursor. The iridium-tantalum dry gel precursor was ground into iridium-tantalum dry gel powder with a mesh size of less than 200 mesh. The iridium-tantalum dry gel powder was calcined, heated to 480°C at a rate of 2°C / min, held at that temperature for 1.5 hours, and then cooled to room temperature at a rate of 3°C / min to obtain a preliminary iridium-tantalum composite oxide nanocrystal. The preliminary iridium-tantalum composite oxide nanocrystal was added to anhydrous ethanol at a solid-liquid ratio of 1:10 and ultrasonically dispersed at 200W for 20 minutes. Then, it was centrifuged at 3000r / min for 5 minutes, and the lower precipitate was collected. The lower precipitate was vacuum dried at 60°C to obtain the iridium-tantalum oxide nanocrystal seed crystal.
[0013] Furthermore, the mixed solvent comprises the following components in mass fractions: Concentrated hydrochloric acid 12%, n-butanol 65%, and isopropanol 23%; The concentrated hydrochloric acid has a mass fraction of 37 wt%.
[0014] Furthermore, the second gradient coating sintering specifically involves: The active layer coating solution is applied to the surface of the tantalum-tin-titanium composite oxide transition layer. Then, it is allowed to stand under a vacuum of -0.07 MPa for 4 minutes to remove bubbles. After that, gradient sintering is performed. First, the temperature is increased from room temperature to 200°C at a rate of 2°C / min and held for 10 minutes. Then, the temperature is increased to 350°C at a rate of 2°C / min and held for 15 minutes. Then, the temperature is increased to 500°C at a rate of 2.5°C / min and held for 12 minutes. After that, the temperature is decreased to 200°C at a rate of 2°C / min and then air-cooled to room temperature. Then, the brushing, degassing and gradient sintering steps are repeated 12 to 14 times.
[0015] Furthermore, the post-processing specifically involves heating to 500°C at a rate of 2°C / min, holding at that temperature for 1 hour, and then allowing the furnace to cool naturally to room temperature.
[0016] The present invention also proposes a coated titanium anode material.
[0017] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. While maintaining the overall high tantalum and low iridium composition, this invention regulates the electronic structure and surface coordination environment of the active sites in the coating by antimony and cerium dual doping. Without increasing the iridium ratio or enhancing the interfacial oxidation, it improves the activity and selectivity of the oxygen evolution reaction, while weakening the adsorption and oxidation of citric acid complexing agents.
[0018] 2. This invention reduces interfacial stress by coating a transition layer, reduces shrinkage cracks by inducing fine grain growth through nano-seed crystals, and gently releases stress through a gradient sintering process. These three factors work together to reduce cracking and improve coating density. Detailed Implementation
[0019] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention. It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the present invention.
[0020] Furthermore, regarding the numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0021] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.
[0022] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.
[0023] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.
[0024] This invention provides a method for preparing a coated titanium anode material, comprising the following preparation steps: The titanium substrate was pretreated and then etched with oxalic acid to obtain the treated titanium substrate. Tantalum pentachloride, tin tetrachloride and titanium tetrachloride were added to n-butanol solution and stirred to dissolve. After ultrasonic dispersion, a transition layer coating solution was obtained. The transition layer coating liquid is applied to the surface of the treated titanium substrate and subjected to first gradient coating sintering to obtain a tantalum-tin-titanium composite oxide transition layer. A mixed solvent is obtained by mixing concentrated hydrochloric acid, n-butanol and isopropanol. Tantalum pentachloride, chloroiridium hexahydrate, antimony trichloride, cerium nitrate hexahydrate and iridium tantalum oxide nanocrystal seed crystals are added to the mixed solvent and dispersed by ultrasonication to obtain an active coating liquid. After the active layer coating solution is applied to the surface of the tantalum-tin-titanium composite oxide transition layer, it is subjected to negative pressure degassing treatment. After treatment, a second gradient coating sintering is performed. After post-treatment, the coated titanium anode material is obtained.
[0025] Specifically, the titanium matrix is preferably a pure titanium sheet.
[0026] Specifically, when preparing the transition layer coating solution, tantalum pentachloride, tin tetrachloride, and titanium tetrachloride are weighed according to the molar ratio of tantalum:tin:titanium = 70:20:10, dissolved in n-butanol solvent, and the total metal salt mass fraction is controlled to be 12%. Then, the solution is ultrasonically dispersed at room temperature for 30 minutes to obtain the transition layer coating solution.
[0027] It is understood that, while maintaining the overall high tantalum and low iridium composition, this invention regulates the electronic structure and surface coordination environment of the active sites in the coating by antimony and cerium dual doping. Without increasing the iridium ratio or enhancing the interfacial oxidation, it improves the activity and selectivity of the oxygen evolution reaction, while weakening the adsorption and oxidation of citric acid complexing agents.
[0028] It is understood that the present invention reduces interfacial stress by coating a transition layer, reduces shrinkage cracks by inducing fine grain growth through nano-seed crystals, and releases stress gradually through a gradient sintering process. These three factors work together to reduce cracking and improve coating density.
[0029] In this invention, the preprocessing specifically includes: After removing the surface oxide scale by sanding the titanium substrate with 800-grit sandpaper, rinse with deionized water, and then sand with 80-120-grit quartz sand at 3-4 kg / m². The titanium substrate was roughened by sandblasting at a certain pressure to control the surface roughness Ra = 3~5μm. The titanium substrate was then placed in a solution of NaOH with a concentration of 40g / L. Concentration of 40g / L The mixture was kept at 75°C for 25 minutes in a 40 g / L alkaline solution, then removed and washed with deionized water until neutral.
[0030] It is understood that the present invention can remove the original oxide scale on the surface of the titanium substrate by mechanically polishing with 800-grit sandpaper to obtain a smooth and uniform substrate surface; then, the substrate surface is roughened by quartz sand blasting to create a rough morphology, increase the effective contact area and form an anchoring structure, providing a good bonding foundation for subsequent coatings; finally, the impurities attached to the substrate surface are removed by the saponification and emulsification of hot alkaline solution.
[0031] In this invention, the oxalic acid etching specifically involves immersing the treated titanium substrate in a 12% (w / w) oxalic acid solution, hot-soaking it at 105°C for 1.5 hours, rinsing it with deionized water until neutral, and then drying it at 105°C.
[0032] It is understood that the present invention uses a high-temperature oxalic acid solution to chemically etch the titanium substrate. On the one hand, this can remove the oxide layer and sand particles remaining on the substrate surface after sandblasting, avoiding damage to the interfacial conductivity and adhesion by impurities and residual oxide film. On the other hand, it can further etch to form a uniform and dense defect structure on the basis of sandblasting roughening, control the surface roughness, and enhance the adhesion between the substrate and the subsequent coating.
[0033] In this invention, the first gradient coating sintering specifically refers to: The transition layer coating solution was brushed onto the treated titanium substrate surface at a coating volume of 0.9 mL / m³. Then, gradient sintering is performed. First, the temperature is increased to 220°C at a rate of 3°C / min and held for 10 min. Then, the temperature is increased to 360°C at a rate of 3°C / min and held for 15 min. Then, the temperature is increased to 510°C at a rate of 2°C / min and held for 25 min. After the process, the temperature is reduced to 200°C in the furnace and then removed and air-cooled to room temperature. The brushing and gradient sintering steps are repeated 3 to 4 times. When performing the last gradient sintering, the holding time at 510°C is extended to 45 min.
[0034] Specifically, the transition layer coating solution is brushed onto the treated titanium substrate surface at a coating volume of 0.9 mL / m³. It is then placed in a muffle furnace for gradient sintering in an air atmosphere: First, heat the temperature to 220℃ at a rate of 3℃ / min, hold for 10min to remove the solvent and form a uniform dry film; Then raise the temperature to 360℃ at a rate of 3℃ / min and hold for 15min to allow the metal chloride to decompose and dechlorinate slowly; Then, the temperature is increased to 510℃ at a rate of 2℃ / min and held for 25 minutes to complete the oxide crystallization and densification; finally, the temperature is reduced to 200℃ in the furnace and then removed and air-cooled to room temperature.
[0035] Repeat the brushing and gradient sintering steps 3 to 4 times. When performing the last gradient sintering, extend the holding time at 510℃ from 25 min to 45 min.
[0036] It is understood that the present invention constructs a uniformly thick tantalum-tin-titanium composite oxide transition layer on the surface of a pretreated titanium substrate through a multi-pass brush coating combined with a gradient sintering process. The gradient sintering process can gradually remove the coating solvent and dechlorinate the metal chloride precursor, avoiding coating bubbling and porosity defects caused by solvent boiling and rapid gas generation. Then, the oxide crystallization and structural densification are completed at 510°C. The final extended high-temperature holding time can improve the crystallinity of the transition layer and the interlayer bonding strength. The transition layer obtained after sintering can match the thermal expansion coefficients of the titanium substrate and the active layer, alleviate interlayer thermal stress, reduce the initiation of interface cracks, and block the penetration of active oxygen into the titanium substrate during electrolysis. At the same time, the maximum sintering temperature is controlled at 510℃ throughout the process, which can effectively prevent the titanium substrate from oxidizing at high temperature to form a loose and highly resistant oxide layer, and ensure the conductivity and bonding stability of the interface.
[0037] In this invention, when tantalum pentachloride, iridium chlorohydrate, antimony trichloride, cerium nitrate hexahydrate, and iridium tantalum oxide nanocrystal seed crystals are added to the mixed solvent: Weigh out tantalum pentachloride and chloroiridium hexahydrate according to the mass ratio of tantalum to iridium = 6.5:3.5; The total molar amount of antimony trichloride and cerium nitrate hexahydrate is 4% of the total molar amount of tantalum pentachloride and chloroiridium hexahydrate, wherein the molar ratio of antimony trichloride and cerium nitrate hexahydrate is 6:4; The mass of the iridium-tantalum oxide nanocrystal seed crystal is 2% of the total mass of tantalum and iridium elements.
[0038] It is understood that this invention sets the ratio of tantalum and iridium main elements at a mass ratio of 6.5:3.5 to maintain the overall composition characteristics of high tantalum and low iridium. At the same time, antimony trichloride and cerium nitrate hexahydrate, accounting for 4% of the total molar amount of the main salt and in a molar ratio of 6:4, are introduced. Antimony can be doped into the iridium oxide lattice to regulate its electronic structure, optimize the adsorption energy of oxygen evolution reaction intermediates, and enhance the intrinsic electrocatalytic activity of the coating. Cerium is enriched at the grain boundaries and coating surface, modifying the interfacial coordination environment and weakening the adsorption and oxidation side reactions of citrate on the electrode surface. At the same time, iridium-tantalum oxide nanocrystal seed crystals, accounting for 2% of the total mass of tantalum and iridium, are added, which can serve as non-uniform nucleation sites during sintering, induce uniform nucleation and fine grain growth of oxide grains, reduce sintering volume shrinkage stress, and reduce coating cracks and porosity defects.
[0039] In this invention, the method for preparing the iridium-tantalum oxide nanocrystal seed crystal is as follows: Tantalum pentachloride and chloroiridium hexahydrate were weighed according to a molar ratio of 1:1 for tantalum and iridium. The tantalum pentachloride was added to concentrated hydrochloric acid with a mass fraction of 37% under ice bath stirring until dissolved, resulting in a mixed solution with a tantalum ion concentration of 0.2 mol / L. The chloroiridium hexahydrate was added to the mixed solution and stirring was continued until dissolved, resulting in a tantalum-iridium mixed metal salt mother liquor. Anhydrous ethanol was added to the mother liquor of the tantalum-iridium mixed metal salt to adjust the total metal ion concentration in the system to 0.1 mol / L. Then, citric acid monohydrate was added to the system at a molar ratio of citric acid monohydrate to total metal ions = 1.2:1 and stirred until completely dissolved to obtain the first mixed solution. The first mixed solution was placed in a water bath at 40°C, and 10% ammonia solution was added dropwise with stirring to adjust the pH of the system to between 3.0 and 3.5. After the addition was completed, the mixture was kept warm and stirred for 30 minutes to obtain an iridium-tantalum composite sol. The iridium-tantalum composite sol was aged in a water bath at 60°C for 12 hours to obtain a wet gel. The wet gel was dried at 105°C for 6 hours to obtain an iridium-tantalum dry gel precursor. The iridium-tantalum dry gel precursor was ground into iridium-tantalum dry gel powder with a mesh size of less than 200 mesh. The iridium-tantalum dry gel powder was calcined, heated to 480°C at a rate of 2°C / min, held at that temperature for 1.5 hours, and then cooled to room temperature at a rate of 3°C / min to obtain a preliminary iridium-tantalum composite oxide nanocrystal. The preliminary iridium-tantalum composite oxide nanocrystal was added to anhydrous ethanol at a solid-liquid ratio of 1:10 and ultrasonically dispersed at 200W for 20 minutes. Then, it was centrifuged at 3000r / min for 5 minutes, and the lower precipitate was collected. The lower precipitate was vacuum dried at 60°C to obtain the iridium-tantalum oxide nanocrystal seed crystal.
[0040] It is understood that during the sintering and crystallization process of the coating, the iridium tantalum oxide nanocrystal seed crystals added in this invention can serve as nucleation cores, inducing the iridium tantalum oxide grains to rapidly nucleate around the seed crystals, replacing the traditional random nucleation, and avoiding the problems of abnormal grain growth and uneven size distribution. This results in a coating structure with finer grains and more uniform structure. At the same time, this crystal structure can also alleviate the internal stress concentration caused by the volume shrinkage of oxides during sintering, thereby reducing the initiation of defects such as cracks and pores in the coating and significantly improving the overall density and structural integrity of the coating.
[0041] In this invention, the mixed solvent comprises the following components by mass fraction: Concentrated hydrochloric acid 12%, n-butanol 65%, and isopropanol 23%; The concentrated hydrochloric acid has a mass fraction of 37 wt%.
[0042] It is understood that the 37% hydrochloric acid in the mixed solvent of this invention provides a strongly acidic medium environment, effectively inhibiting the hydrolysis and precipitation of metal chlorides such as tantalum pentachloride during preparation and storage, ensuring the uniformity and transparency of the coating solution and the stability of its components; n-butanol is the main solvent, with a moderate boiling point and evaporation rate, which can control the viscosity and leveling properties of the coating solution, so that the coating solution is evenly spread on the substrate surface during brushing, avoiding sagging or local dry spots; the introduction of isopropanol can improve the wetting ability of the coating solution on the rough titanium substrate, and at the same time, the gradient sintering process can achieve the smooth and orderly evaporation of the solvent, reducing pinholes and pitting defects in the coating caused by solvent boiling and rapid removal.
[0043] Specifically, the preparation method of the active coating liquid of the present invention is as follows: S1. Weigh out 37wt% concentrated hydrochloric acid, n-butanol and isopropanol according to the mass fraction of the mixed solvent, stir and mix them at room temperature, place them in an ice-water bath, and cool them to 0~5℃ to obtain the mixed solvent. S2. Weigh tantalum pentachloride and chloroiridium hexahydrate according to the molar ratio of tantalum to iridium = 6.5:3.5. Weigh the mixed solvent according to the mass ratio of total mass of tantalum pentachloride and chloroiridium hexahydrate to mixed solvent = 1:10. Add the tantalum pentachloride to the pre-cooled mixed solvent under ice bath stirring and stir until completely dissolved. Then add chloroiridium hexahydrate to the solution and continue stirring until completely dissolved to obtain an iridium-tantalum mixed solution. S3. Based on the total molar amount of tantalum pentachloride and chloroiridium hexahydrate, weigh antimony trichloride and cerium nitrate hexahydrate at a ratio of 4% of the total molar amount of antimony trichloride and cerium nitrate hexahydrate, wherein the molar ratio of antimony trichloride to cerium nitrate hexahydrate is 6:4. Add the antimony trichloride and cerium nitrate hexahydrate sequentially to the iridium-tantalum mixed solution and stir continuously for 20 minutes to obtain the iridium-tantalum-antimony-cerium mixed solution. S4. Weigh 2% of the total mass of tantalum pentachloride and iridium hexahydrate containing tantalum and iridium elements into iridium oxide nanocrystal seed crystals, add them to the iridium-tantalum-antimony-cerium mixed solution, first mechanically stir for 5 min, then ultrasonically disperse at room temperature with a power of 200W for 40 min to obtain the active coating solution.
[0044] In this invention, the second gradient coating sintering specifically comprises: The active layer coating solution is applied to the surface of the tantalum-tin-titanium composite oxide transition layer. Then, it is allowed to stand under a vacuum of -0.07 MPa for 4 minutes to remove bubbles. After that, gradient sintering is performed. First, the temperature is increased from room temperature to 200°C at a rate of 2°C / min and held for 10 minutes. Then, the temperature is increased to 350°C at a rate of 2°C / min and held for 15 minutes. Then, the temperature is increased to 500°C at a rate of 2.5°C / min and held for 12 minutes. After that, the temperature is decreased to 200°C at a rate of 2°C / min and then air-cooled to room temperature. The brushing, degassing and gradient sintering steps are repeated 12 to 14 times. The preferred number of repetitions is 13 times.
[0045] Specifically, the amount of the active coating solution applied to the surface of the tantalum-tin-titanium composite oxide transition layer in a single brush pass is 0.8 mL / s. It was then immediately placed in a vacuum drying oven, with the vacuum level controlled at -0.07 MPa, and allowed to stand for 4 minutes to remove air bubbles trapped in the coating liquid. It was then placed in a muffle furnace for gradient sintering in an air atmosphere. First, raise the temperature from room temperature to 200℃ at a rate of 2℃ / min, hold for 10min, and slowly remove the low-boiling-point solvent to avoid the solvent from boiling violently and forming pores. Then, the temperature is increased to 350℃ at a rate of 2℃ / min and held for 15min to allow the metal chloride precursor to gradually decompose and dechlorinate. Then, the temperature is increased to 500℃ at a rate of 2.5℃ / min and held for 12 min to complete oxide crystallization and grain growth. Then, it was cooled to 200°C at a rate of 2°C / min and then removed and air-cooled to room temperature.
[0046] Repeat the brush coating, vacuum degassing, and gradient sintering steps 12 to 14 times.
[0047] It is understood that this invention prepares a uniform and dense iridium-tantalum active coating layer by layer through a multi-pass repeated brushing-vacuum degassing-gradient sintering cycle process; quantitative brushing can control the thickness of a single wet film, ensuring the uniformity of coating composition and thickness; vacuum degassing can remove air bubbles trapped during the brushing process; the three-stage gradient sintering can sequentially and gradually remove low-boiling-point solvents, gradually decompose and dechlorinate the metal chloride precursor, and finally complete oxide crystallization and grain growth, effectively avoiding bubbling and microcrack defects caused by solvent boiling and rapid gas generation, while alleviating thermal stress concentration and achieving fine grain densification; after 12 to 14 cycles of layer-by-layer accumulation, a complete active coating of the target thickness can be obtained under the premise of ensuring sufficient crystallization of a single coating and strong interlayer bonding, effectively avoiding the volume shrinkage and cracking problem caused by single thick coating.
[0048] In this invention, the post-processing specifically involves heating to 500°C at a rate of 2°C / min, holding at that temperature for 1 hour, and then allowing the furnace to cool naturally to room temperature.
[0049] Understandably, this post-treatment, by slowly heating to 500℃ at a rate of 2℃ / min and holding for 1 hour, can effectively eliminate interlayer interface defects and accumulated internal stresses generated by multi-pass layer-by-layer coating and sintering, and strengthen the interfacial bonding strength between each layer and between the active layer and the transition layer; at the same time, it can improve the crystal integrity of the iridium-tantalum oxide phase, optimize the stability of the coating's electrical conductivity and catalytic activity, and promote the uniform diffusion distribution of antimony and cerium dopants at the lattice and grain boundaries; subsequent natural cooling with the furnace can avoid thermal stress cracks caused by excessively rapid cooling.
[0050] The present invention also provides a coated titanium anode material.
[0051] Example 1 S1. Using industrial pure titanium TA1 sheet as the titanium substrate, the substrate is polished with 800-grit sandpaper to remove the surface oxide scale, then rinsed with deionized water, and subsequently sanded with 80-grit quartz sand at 3 kg / m². The titanium substrate was roughened by sandblasting at a certain pressure to control the surface roughness Ra = 3~5μm. The titanium substrate was then placed in a solution of NaOH with a concentration of 40g / L. Concentration of 40g / L The titanium matrix was heated in a mixed alkaline solution with a concentration of 40 g / L at 75°C for 25 min, then removed and washed with deionized water until neutral. The washed titanium matrix was then immersed in a 12% oxalic acid solution at 105°C for 1.5 h. After being removed, it was rinsed with deionized water until neutral and then dried at 105°C to obtain the pretreated titanium matrix. S2. Weigh tantalum pentachloride, tin tetrachloride, and titanium tetrachloride according to the molar ratio of tantalum:tin:titanium = 70:20:10, dissolve them in n-butanol solvent, control the total metal salt mass fraction to be 12%, and then ultrasonically disperse them at room temperature for 30 min to obtain the transition layer coating solution. S3. The transition layer coating solution is brushed onto the treated titanium substrate surface, with a coating amount of 0.9 mL / m³. It is then placed in a muffle furnace for gradient sintering in an air atmosphere: First, raise the temperature to 220℃ at a rate of 3℃ / min and hold for 10 min; then raise the temperature to 360℃ at a rate of 3℃ / min and hold for 15 min; then raise the temperature to 510℃ at a rate of 2℃ / min and hold for 25 min; finally, cool the furnace to 200℃ and remove it for air cooling to room temperature. Repeat the brush coating and gradient sintering steps three times. During the last gradient sintering, the holding time at 510℃ was extended from 25 min to 45 min to obtain a tantalum-tin-titanium composite oxide transition layer. S4. Weigh out 37wt% concentrated hydrochloric acid, n-butanol and isopropanol according to the mass fractions of 12% concentrated hydrochloric acid, 65% n-butanol and 23% isopropanol. Stir and mix them at room temperature and place them in an ice water bath to cool to 0~5℃ to obtain a mixed solvent. S5. Weigh tantalum pentachloride and chloroiridium hexahydrate according to the molar ratio of tantalum to iridium = 6.5:3.5. Weigh the mixed solvent according to the mass ratio of total mass of tantalum pentachloride and chloroiridium hexahydrate to mixed solvent = 1:10. Add the tantalum pentachloride to the pre-cooled mixed solvent under ice bath stirring and stir until completely dissolved. Then add chloroiridium hexahydrate to the solution and continue stirring until completely dissolved to obtain an iridium-tantalum mixed solution. S6. Based on the total molar amount of tantalum pentachloride and chloroiridic acid hexahydrate, weigh antimony trichloride and cerium nitrate hexahydrate at a ratio of 4% of the total molar amount of antimony trichloride and cerium nitrate hexahydrate, wherein the molar ratio of antimony trichloride to cerium nitrate hexahydrate is 6:4. Add the antimony trichloride and cerium nitrate hexahydrate sequentially to the iridium-tantalum mixed solution and stir continuously for 20 minutes to obtain the iridium-tantalum-antimony-cerium mixed solution. S7. Weigh 2% of the total mass of tantalum pentachloride and iridium hexahydrate containing tantalum and iridium elements into iridium oxide nanocrystal seed crystals, add them to the iridium-tantalum-antimony-cerium mixed solution, first mechanically stir for 5 min, then ultrasonically disperse at room temperature with a power of 200W for 40 min to obtain the active coating solution.
[0052] S8. The active coating solution is applied to the surface of the tantalum-tin-titanium composite oxide transition layer by brushing, with a single brush application amount of 0.8 mL / s. It was then immediately placed in a vacuum drying oven, with the vacuum level controlled at -0.07 MPa, and allowed to stand for 4 minutes. Afterward, it was placed in a muffle furnace for gradient sintering in an air atmosphere. First, the temperature is increased from room temperature to 200℃ at a rate of 2℃ / min and held for 10 min; then increased to 350℃ at a rate of 2℃ / min and held for 15 min; then increased to 500℃ at a rate of 2.5℃ / min and held for 12 min; then decreased to 200℃ at a rate of 2℃ / min and removed and air-cooled to room temperature; the brush coating, vacuum degassing and gradient sintering steps are repeated 12 times. After coating, the coated titanium substrate is heated to 500℃ at a rate of 2℃ / min and held for 1 h, and then naturally cooled to room temperature with the furnace to obtain the coated titanium anode material.
[0053] Example 2 S1. Using industrial pure titanium TA1 sheet as the titanium substrate, the substrate is polished with 800-grit sandpaper to remove the surface oxide scale, then rinsed with deionized water, and subsequently sanded with 120-grit quartz sand at 4 kg / m². The titanium substrate was roughened by sandblasting at a certain pressure to control the surface roughness Ra = 3~5μm. The titanium substrate was then placed in a solution of NaOH with a concentration of 40g / L. Concentration of 40g / L The titanium matrix was heated in a mixed alkaline solution with a concentration of 40 g / L at 75°C for 25 min, then removed and washed with deionized water until neutral. The washed titanium matrix was then immersed in a 12% oxalic acid solution at 105°C for 1.5 h. After being removed, it was rinsed with deionized water until neutral and then dried at 105°C to obtain the pretreated titanium matrix. S2. Weigh tantalum pentachloride, tin tetrachloride, and titanium tetrachloride according to the molar ratio of tantalum:tin:titanium = 70:20:10, dissolve them in n-butanol solvent, control the total metal salt mass fraction to be 12%, and then ultrasonically disperse them at room temperature for 30 min to obtain the transition layer coating solution. S3. The transition layer coating solution is brushed onto the treated titanium substrate surface, with a coating amount of 0.9 mL / m³. It is then placed in a muffle furnace for gradient sintering in an air atmosphere: First, raise the temperature to 220℃ at a rate of 3℃ / min and hold for 10 min; then raise the temperature to 360℃ at a rate of 3℃ / min and hold for 15 min; then raise the temperature to 510℃ at a rate of 2℃ / min and hold for 25 min; finally, cool the furnace to 200℃ and remove it for air cooling to room temperature. The brush coating and gradient sintering steps were repeated 4 times. During the last gradient sintering, the holding time at 510℃ was extended from 25 min to 45 min to obtain a tantalum-tin-titanium composite oxide transition layer. S4. Weigh out 37wt% concentrated hydrochloric acid, n-butanol and isopropanol according to the mass fractions of 12% concentrated hydrochloric acid, 65% n-butanol and 23% isopropanol. Stir and mix them at room temperature and place them in an ice water bath to cool to 0~5℃ to obtain a mixed solvent. S5. Weigh tantalum pentachloride and chloroiridium hexahydrate according to the molar ratio of tantalum to iridium = 6.5:3.5. Weigh the mixed solvent according to the mass ratio of total mass of tantalum pentachloride and chloroiridium hexahydrate to mixed solvent = 1:10. Add the tantalum pentachloride to the pre-cooled mixed solvent under ice bath stirring and stir until completely dissolved. Then add chloroiridium hexahydrate to the solution and continue stirring until completely dissolved to obtain an iridium-tantalum mixed solution. S6. Based on the total molar amount of tantalum pentachloride and chloroiridic acid hexahydrate, weigh antimony trichloride and cerium nitrate hexahydrate at a ratio of 4% of the total molar amount of antimony trichloride and cerium nitrate hexahydrate, wherein the molar ratio of antimony trichloride to cerium nitrate hexahydrate is 6:4. Add the antimony trichloride and cerium nitrate hexahydrate sequentially to the iridium-tantalum mixed solution and stir continuously for 20 minutes to obtain the iridium-tantalum-antimony-cerium mixed solution. S7. Weigh 2% of the total mass of tantalum pentachloride and iridium hexahydrate containing tantalum and iridium elements into iridium oxide nanocrystal seed crystals, add them to the iridium-tantalum-antimony-cerium mixed solution, first mechanically stir for 5 min, then ultrasonically disperse at room temperature with a power of 200W for 40 min to obtain the active coating solution.
[0054] S8. The active coating solution is applied to the surface of the tantalum-tin-titanium composite oxide transition layer by brushing, with a single brush application amount of 0.8 mL / s. It was then immediately placed in a vacuum drying oven, with the vacuum level controlled at -0.07 MPa, and allowed to stand for 4 minutes. Afterward, it was placed in a muffle furnace for gradient sintering in an air atmosphere. First, the temperature is increased from room temperature to 200℃ at a rate of 2℃ / min and held for 10 min; then increased to 350℃ at a rate of 2℃ / min and held for 15 min; then increased to 500℃ at a rate of 2.5℃ / min and held for 12 min; then decreased to 200℃ at a rate of 2℃ / min and removed for air cooling to room temperature; the brush coating, vacuum degassing and gradient sintering steps are repeated 13 times. After coating, the coated titanium substrate is heated to 500℃ at a rate of 2℃ / min and held for 1 h, and then naturally cooled to room temperature with the furnace to obtain the coated titanium anode material.
[0055] Example 3 S1. Using industrial pure titanium TA1 sheet as the titanium substrate, the substrate is polished with 800-grit sandpaper to remove the surface oxide scale, then rinsed with deionized water, and subsequently sanded with 120-grit quartz sand at 4 kg / m². The titanium substrate was roughened by sandblasting at a certain pressure to control the surface roughness Ra = 3~5μm. The titanium substrate was then placed in a solution of NaOH with a concentration of 40g / L. Concentration of 40g / L The titanium matrix was heated in a mixed alkaline solution with a concentration of 40 g / L at 75°C for 25 min, then removed and washed with deionized water until neutral. The washed titanium matrix was then immersed in a 12% oxalic acid solution at 105°C for 1.5 h. After being removed, it was rinsed with deionized water until neutral and then dried at 105°C to obtain the pretreated titanium matrix. S2. Weigh tantalum pentachloride, tin tetrachloride, and titanium tetrachloride according to the molar ratio of tantalum:tin:titanium = 70:20:10, dissolve them in n-butanol solvent, control the total metal salt mass fraction to be 12%, and then ultrasonically disperse them at room temperature for 30 min to obtain the transition layer coating solution. S3. The transition layer coating solution is brushed onto the treated titanium substrate surface, with a coating amount of 0.9 mL / m³. It is then placed in a muffle furnace for gradient sintering in an air atmosphere: First, raise the temperature to 220℃ at a rate of 3℃ / min and hold for 10 min; then raise the temperature to 360℃ at a rate of 3℃ / min and hold for 15 min; then raise the temperature to 510℃ at a rate of 2℃ / min and hold for 25 min; finally, cool the furnace to 200℃ and remove it for air cooling to room temperature. The brush coating and gradient sintering steps were repeated 4 times. During the last gradient sintering, the holding time at 510℃ was extended from 25 min to 45 min to obtain a tantalum-tin-titanium composite oxide transition layer. S4. Weigh out 37wt% concentrated hydrochloric acid, n-butanol and isopropanol according to the mass fractions of 12% concentrated hydrochloric acid, 65% n-butanol and 23% isopropanol. Stir and mix them at room temperature and place them in an ice water bath to cool to 0~5℃ to obtain a mixed solvent. S5. Weigh tantalum pentachloride and chloroiridium hexahydrate according to the molar ratio of tantalum to iridium = 6.5:3.5. Weigh the mixed solvent according to the mass ratio of total mass of tantalum pentachloride and chloroiridium hexahydrate to mixed solvent = 1:10. Add the tantalum pentachloride to the pre-cooled mixed solvent under ice bath stirring and stir until completely dissolved. Then add chloroiridium hexahydrate to the solution and continue stirring until completely dissolved to obtain an iridium-tantalum mixed solution. S6. Based on the total molar amount of tantalum pentachloride and chloroiridic acid hexahydrate, weigh antimony trichloride and cerium nitrate hexahydrate at a ratio of 4% of the total molar amount of antimony trichloride and cerium nitrate hexahydrate, wherein the molar ratio of antimony trichloride to cerium nitrate hexahydrate is 6:4. Add the antimony trichloride and cerium nitrate hexahydrate sequentially to the iridium-tantalum mixed solution and stir continuously for 20 minutes to obtain the iridium-tantalum-antimony-cerium mixed solution. S7. Weigh 2% of the total mass of tantalum pentachloride and iridium hexahydrate containing tantalum and iridium elements into iridium oxide nanocrystal seed crystals, add them to the iridium-tantalum-antimony-cerium mixed solution, first mechanically stir for 5 min, then ultrasonically disperse at room temperature with a power of 200W for 40 min to obtain the active coating solution.
[0056] S8. The active coating solution is applied to the surface of the tantalum-tin-titanium composite oxide transition layer by brushing, with a single brush application amount of 0.8 mL / s. It was then immediately placed in a vacuum drying oven, with the vacuum level controlled at -0.07 MPa, and allowed to stand for 4 minutes. Afterward, it was placed in a muffle furnace for gradient sintering in an air atmosphere. First, the temperature is increased from room temperature to 200℃ at a rate of 2℃ / min and held for 10 min; then increased to 350℃ at a rate of 2℃ / min and held for 15 min; then increased to 500℃ at a rate of 2.5℃ / min and held for 12 min; then decreased to 200℃ at a rate of 2℃ / min and removed for air cooling to room temperature; the brush coating, vacuum degassing and gradient sintering steps are repeated 14 times. After coating, the coated titanium substrate is heated to 500℃ at a rate of 2℃ / min and held for 1 h, and then naturally cooled to room temperature with the furnace to obtain the coated titanium anode material.
[0057] Comparative Example 1 The coated titanium anode material prepared according to Example 2 disclosed in patent CN121344574B; Comparative Example 2 (without introducing Sb and Ce elements) S1. Using industrial pure titanium TA1 sheet as the titanium substrate, the substrate is polished with 800-grit sandpaper to remove the surface oxide scale, then rinsed with deionized water, and subsequently sanded with 120-grit quartz sand at 4 kg / m². The titanium substrate was roughened by sandblasting at a certain pressure to control the surface roughness Ra = 3~5μm. The titanium substrate was then placed in a solution of NaOH with a concentration of 40g / L. Concentration of 40g / L The titanium matrix was heated in a mixed alkaline solution with a concentration of 40 g / L at 75°C for 25 min, then removed and washed with deionized water until neutral. The washed titanium matrix was then immersed in a 12% oxalic acid solution at 105°C for 1.5 h. After being removed, it was rinsed with deionized water until neutral and then dried at 105°C to obtain the pretreated titanium matrix. S2. Weigh tantalum pentachloride, tin tetrachloride, and titanium tetrachloride according to the molar ratio of tantalum:tin:titanium = 70:20:10, dissolve them in n-butanol solvent, control the total metal salt mass fraction to be 12%, and then ultrasonically disperse them at room temperature for 30 min to obtain the transition layer coating solution. S3. The transition layer coating solution is brushed onto the treated titanium substrate surface, with a coating amount of 0.9 mL / m³. It is then placed in a muffle furnace for gradient sintering in an air atmosphere: First, raise the temperature to 220℃ at a rate of 3℃ / min and hold for 10 min; then raise the temperature to 360℃ at a rate of 3℃ / min and hold for 15 min; then raise the temperature to 510℃ at a rate of 2℃ / min and hold for 25 min; finally, cool the furnace to 200℃ and remove it for air cooling to room temperature. The brush coating and gradient sintering steps were repeated 4 times. During the last gradient sintering, the holding time at 510℃ was extended from 25 min to 45 min to obtain a tantalum-tin-titanium composite oxide transition layer. S4. Weigh out 37wt% concentrated hydrochloric acid, n-butanol and isopropanol according to the mass fractions of 12% concentrated hydrochloric acid, 65% n-butanol and 23% isopropanol. Stir and mix them at room temperature and place them in an ice water bath to cool to 0~5℃ to obtain a mixed solvent. S5. Weigh tantalum pentachloride and chloroiridium hexahydrate according to the molar ratio of tantalum to iridium = 6.5:3.5. Weigh the mixed solvent according to the mass ratio of total mass of tantalum pentachloride and chloroiridium hexahydrate to mixed solvent = 1:10. Add the tantalum pentachloride to the pre-cooled mixed solvent under ice bath stirring and stir until completely dissolved. Then add chloroiridium hexahydrate to the solution and continue stirring until completely dissolved to obtain an iridium-tantalum mixed solution. S6. Weigh 2% of the total mass of tantalum pentachloride and iridium hexahydrate containing tantalum and iridium elements into iridium oxide nanocrystal seed crystals, add them to the iridium-tantalum mixed solution, first mechanically stir for 5 min, then ultrasonically disperse at room temperature with a power of 200W for 40 min to obtain the active coating solution.
[0058] S7. The active coating solution is applied to the surface of the tantalum-tin-titanium composite oxide transition layer by brushing, with a single brush application amount of 0.8 mL / s. It was then immediately placed in a vacuum drying oven, with the vacuum level controlled at -0.07 MPa, and allowed to stand for 4 minutes. Afterward, it was placed in a muffle furnace for gradient sintering in an air atmosphere. First, the temperature is increased from room temperature to 200℃ at a rate of 2℃ / min and held for 10 min; then increased to 350℃ at a rate of 2℃ / min and held for 15 min; then increased to 500℃ at a rate of 2.5℃ / min and held for 12 min; then decreased to 200℃ at a rate of 2℃ / min and removed for air cooling to room temperature; the brush coating, vacuum degassing and gradient sintering steps are repeated 13 times. After coating, the coated titanium substrate is heated to 500℃ at a rate of 2℃ / min and held for 1 h, and then naturally cooled to room temperature with the furnace to obtain the coated titanium anode material.
[0059] Comparative Example 3 (without introducing iridium tantalum oxide nanocrystal seed crystals) S1. Using industrial pure titanium TA1 sheet as the titanium substrate, the substrate is polished with 800-grit sandpaper to remove the surface oxide scale, then rinsed with deionized water, and subsequently sanded with 120-grit quartz sand at 4 kg / m². The titanium substrate was roughened by sandblasting at a certain pressure to control the surface roughness Ra = 3~5μm. The titanium substrate was then placed in a solution of NaOH with a concentration of 40g / L. Concentration of 40g / L The titanium matrix was heated in a mixed alkaline solution with a concentration of 40 g / L at 75°C for 25 min, then removed and washed with deionized water until neutral. The washed titanium matrix was then immersed in a 12% oxalic acid solution at 105°C for 1.5 h. After being removed, it was rinsed with deionized water until neutral and then dried at 105°C to obtain the pretreated titanium matrix. S2. Weigh tantalum pentachloride, tin tetrachloride, and titanium tetrachloride according to the molar ratio of tantalum:tin:titanium = 70:20:10, dissolve them in n-butanol solvent, control the total metal salt mass fraction to be 12%, and then ultrasonically disperse them at room temperature for 30 min to obtain the transition layer coating solution. S3. The transition layer coating solution is brushed onto the treated titanium substrate surface, with a coating amount of 0.9 mL / m³. It is then placed in a muffle furnace for gradient sintering in an air atmosphere: First, raise the temperature to 220℃ at a rate of 3℃ / min and hold for 10 min; then raise the temperature to 360℃ at a rate of 3℃ / min and hold for 15 min; then raise the temperature to 510℃ at a rate of 2℃ / min and hold for 25 min; finally, cool the furnace to 200℃ and remove it for air cooling to room temperature. The brush coating and gradient sintering steps were repeated 4 times. During the last gradient sintering, the holding time at 510℃ was extended from 25 min to 45 min to obtain a tantalum-tin-titanium composite oxide transition layer. S4. Weigh out 37wt% concentrated hydrochloric acid, n-butanol and isopropanol according to the mass fractions of 12% concentrated hydrochloric acid, 65% n-butanol and 23% isopropanol. Stir and mix them at room temperature and place them in an ice water bath to cool to 0~5℃ to obtain a mixed solvent. S5. Weigh tantalum pentachloride and chloroiridium hexahydrate according to the molar ratio of tantalum to iridium = 6.5:3.5. Weigh the mixed solvent according to the mass ratio of total mass of tantalum pentachloride and chloroiridium hexahydrate to mixed solvent = 1:10. Add the tantalum pentachloride to the pre-cooled mixed solvent under ice bath stirring and stir until completely dissolved. Then add chloroiridium hexahydrate to the solution and continue stirring until completely dissolved to obtain an iridium-tantalum mixed solution. S6. Based on the total molar amount of tantalum pentachloride and chloroiridic acid hexahydrate, weigh antimony trichloride and cerium nitrate hexahydrate at a ratio of 4% of the total molar amount of antimony trichloride and cerium nitrate hexahydrate, wherein the molar ratio of antimony trichloride to cerium nitrate hexahydrate is 6:4. Add the antimony trichloride and cerium nitrate hexahydrate sequentially to the iridium-tantalum mixed solution and stir continuously for 20 minutes to obtain the active layer coating solution. S7. The active coating solution is applied to the surface of the tantalum-tin-titanium composite oxide transition layer by brushing, with a single brush application amount of 0.8 mL / s. It was then immediately placed in a vacuum drying oven, with the vacuum level controlled at -0.07 MPa, and allowed to stand for 4 minutes. Afterward, it was placed in a muffle furnace for gradient sintering in an air atmosphere. First, the temperature is increased from room temperature to 200℃ at a rate of 2℃ / min and held for 10 min; then increased to 350℃ at a rate of 2℃ / min and held for 15 min; then increased to 500℃ at a rate of 2.5℃ / min and held for 12 min; then decreased to 200℃ at a rate of 2℃ / min and removed for air cooling to room temperature; the brush coating, vacuum degassing and gradient sintering steps are repeated 13 times. After coating, the coated titanium substrate is heated to 500℃ at a rate of 2℃ / min and held for 1 h, and then naturally cooled to room temperature with the furnace to obtain the coated titanium anode material.
[0060] Comparative Example 4 (The tantalum-tin-titanium composite oxide transition layer was sintered at a high temperature of 610℃) S1. Using industrial pure titanium TA1 sheet as the titanium substrate, the substrate is polished with 800-grit sandpaper to remove the surface oxide scale, then rinsed with deionized water, and subsequently sanded with 120-grit quartz sand at 4 kg / m². The titanium substrate was roughened by sandblasting at a certain pressure to control the surface roughness Ra = 3~5μm. The titanium substrate was then placed in a solution of NaOH with a concentration of 40g / L. Concentration of 40g / L The titanium matrix was heated in a mixed alkaline solution with a concentration of 40 g / L at 75°C for 25 min, then removed and washed with deionized water until neutral. The washed titanium matrix was then immersed in a 12% oxalic acid solution at 105°C for 1.5 h. After being removed, it was rinsed with deionized water until neutral and then dried at 105°C to obtain the pretreated titanium matrix. S2. Weigh tantalum pentachloride, tin tetrachloride, and titanium tetrachloride according to the molar ratio of tantalum:tin:titanium = 70:20:10, dissolve them in n-butanol solvent, control the total metal salt mass fraction to be 12%, and then ultrasonically disperse them at room temperature for 30 min to obtain the transition layer coating solution. S3. The transition layer coating solution is brushed onto the treated titanium substrate surface, with a coating amount of 0.9 mL / m³. It is then placed in a muffle furnace for gradient sintering in an air atmosphere: First, heat the furnace to 220℃ at a rate of 3℃ / min and hold for 10 min; then heat the furnace to 360℃ at a rate of 3℃ / min and hold for 15 min; then heat the furnace to 610℃ at a rate of 2℃ / min and hold for 25 min; finally, cool the furnace to 200℃ and remove the furnace for air cooling to room temperature. The brush coating and gradient sintering steps were repeated 4 times. During the last gradient sintering, the holding time at 610℃ was extended from 25 min to 45 min to obtain a tantalum-tin-titanium composite oxide transition layer. S4. Weigh out 37wt% concentrated hydrochloric acid, n-butanol and isopropanol according to the mass fractions of 12% concentrated hydrochloric acid, 65% n-butanol and 23% isopropanol. Stir and mix them at room temperature and place them in an ice water bath to cool to 0~5℃ to obtain a mixed solvent. S5. Weigh tantalum pentachloride and chloroiridium hexahydrate according to the molar ratio of tantalum to iridium = 6.5:3.5. Weigh the mixed solvent according to the mass ratio of total mass of tantalum pentachloride and chloroiridium hexahydrate to mixed solvent = 1:10. Add the tantalum pentachloride to the pre-cooled mixed solvent under ice bath stirring and stir until completely dissolved. Then add chloroiridium hexahydrate to the solution and continue stirring until completely dissolved to obtain an iridium-tantalum mixed solution. S6. Based on the total molar amount of tantalum pentachloride and chloroiridic acid hexahydrate, weigh antimony trichloride and cerium nitrate hexahydrate at a ratio of 4% of the total molar amount of antimony trichloride and cerium nitrate hexahydrate, wherein the molar ratio of antimony trichloride to cerium nitrate hexahydrate is 6:4. Add the antimony trichloride and cerium nitrate hexahydrate sequentially to the iridium-tantalum mixed solution and stir continuously for 20 minutes to obtain the iridium-tantalum-antimony-cerium mixed solution. S7. Weigh 2% of the total mass of tantalum pentachloride and iridium hexahydrate containing tantalum and iridium elements into iridium oxide nanocrystal seed crystals, add them to the iridium-tantalum-antimony-cerium mixed solution, first mechanically stir for 5 min, then ultrasonically disperse at room temperature with a power of 200W for 40 min to obtain the active coating solution.
[0061] S8. The active coating solution is applied to the surface of the tantalum-tin-titanium composite oxide transition layer by brushing, with a single brush application amount of 0.8 mL / s. It was then immediately placed in a vacuum drying oven, with the vacuum level controlled at -0.07 MPa, and allowed to stand for 4 minutes. Afterward, it was placed in a muffle furnace for gradient sintering in an air atmosphere. First, the temperature is increased from room temperature to 200℃ at a rate of 2℃ / min and held for 10 min; then increased to 350℃ at a rate of 2℃ / min and held for 15 min; then increased to 500℃ at a rate of 2.5℃ / min and held for 12 min; then decreased to 200℃ at a rate of 2℃ / min and removed for air cooling to room temperature; the brush coating, vacuum degassing and gradient sintering steps are repeated 13 times. After coating, the coated titanium substrate is heated to 500℃ at a rate of 2℃ / min and held for 1 h, and then naturally cooled to room temperature with the furnace to obtain the coated titanium anode material.
[0062] Test case Electroplating performance tests were conducted using the coated titanium anode materials from Examples 1-3 and Comparative Examples 1-4: Electroplating system: Alkaline nickel-tungsten citrate plating solution, pH=7.1~7.3; Current density: 9A / Electroplating temperature: 72℃; Accelerated aging capacity: 400Ah; Test metrics: (1) Average current efficiency (%): characterizes electrocatalytic activity; (2) Residual citric acid retention rate in the plating solution after 400Ah (%): The higher the value, the less complexing agent decomposes and the better the inhibition effect; (3) Number of microcracks on the coating surface (strips / ) The lower the value, the better the density. (4) Interfacial resistance of titanium matrix (mΩ·m) The lower the value, the lower the degree of matrix oxidation and the better the conductivity. (5) Anodic enhancement life (h): Constant pressure accelerated oxygen evolution failure life.
[0063] The test results are shown in Table 1: Table 1 Electroplating performance test results ; As can be seen, compared with Comparative Example 1, the average current efficiency of the three sets of embodiments of the present invention is improved by 6.5~8.2 percentage points, and the citric acid retention rate at 400Ah is improved by 10.7~11.8 percentage points, indicating that antimony-cerium dual doping can significantly improve oxygen evolution catalytic activity while maintaining a high tantalum ratio and inhibiting the decomposition of complexing agents; at the same time, the number of microcracks in the embodiments is only 1 / Around, far lower than the 11.4 items in Comparative Example 1. The interface resistance is only 12mΩ. The top and bottom layers offer superior performance compared to the 32.8 mΩ achieved by the high-temperature transition layer. .
[0064] In Comparative Example 2, the current efficiency dropped to 26.3% without antimony and cerium co-doping, and the citric acid retention rate decreased significantly, indicating that Sb-Ce co-doping can achieve high activity and low complexing agent oxidation; the undoped system cannot achieve catalytic performance by relying solely on high tantalum content.
[0065] In Comparative Example 3, after removing the nanocrystal seed crystals, the number of microcracks surged to 9.7 / 100. The enhanced lifespan was significantly shortened to 1080h, proving that iridium-tantalum nanoseed crystals can suppress sintering cracks from the grain nucleation source, greatly improving the coating density and long-term impermeability.
[0066] Comparative Example 4 only increased the sintering temperature of the transition layer to 610℃, while keeping the other processes unchanged. The interfacial resistivity of the matrix directly increased to 31.5 mΩ·m. The significant decrease in lifespan indicates that the low-temperature transition layer at 510℃ can effectively avoid the defect of high-temperature oxidation of TA1 titanium matrix to form a loose and high-resistivity TiO2 oxide scale.
[0067] Comparison of three sets of internal embodiments of the present invention: as the number of coating passes of the active layer increases from 12 to 14, the total coating thickness gradually increases, the total number of active sites increases, the current efficiency, citric acid retention rate and strengthening life are simultaneously slightly improved, and the number of microcracks continues to decrease; the 13-pass and 14-pass coatings have the best overall performance.
[0068] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention can have various modifications and variations. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention. Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the specific implementation of the present invention. Any modifications or equivalent substitutions that do not depart from the spirit and scope of the present invention should be covered within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a coated titanium anode material, characterized in that, The preparation steps include the following: The titanium substrate was pretreated and then etched with oxalic acid to obtain the treated titanium substrate. Tantalum pentachloride, tin tetrachloride and titanium tetrachloride were added to n-butanol solution and stirred to dissolve. After ultrasonic dispersion, a transition layer coating solution was obtained. The transition layer coating liquid is applied to the surface of the treated titanium substrate and subjected to first gradient coating sintering to obtain a tantalum-tin-titanium composite oxide transition layer. A mixed solvent is obtained by mixing concentrated hydrochloric acid, n-butanol and isopropanol. Tantalum pentachloride, chloroiridium hexahydrate, antimony trichloride, cerium nitrate hexahydrate and iridium tantalum oxide nanocrystal seed crystals are added to the mixed solvent and dispersed by ultrasonication to obtain an active coating liquid. After the active layer coating solution is applied to the surface of the tantalum-tin-titanium composite oxide transition layer, it is subjected to negative pressure degassing treatment. After treatment, a second gradient coating sintering is performed. After post-treatment, the coated titanium anode material is obtained. The first gradient coating sintering specifically involves brushing the transition layer coating solution onto the treated titanium substrate surface at a coating amount of 0.9 mL / m³. Then, gradient sintering is performed. First, the temperature is increased to 220℃ at a rate of 3℃ / min and held for 10min. Then, the temperature is increased to 360℃ at a rate of 3℃ / min and held for 15min. Then, the temperature is increased to 510℃ at a rate of 2℃ / min and held for 25min. After the end, the temperature is reduced to 200℃ in the furnace and then removed and air-cooled to room temperature. Then, the brush coating and gradient sintering steps are repeated 3 to 4 times. When performing the last gradient sintering, the holding time at 510℃ is extended to 45min. The second gradient coating sintering specifically involves: The active layer coating solution is applied to the surface of the tantalum-tin-titanium composite oxide transition layer. Then, it is allowed to stand under a vacuum of -0.07 MPa for 4 min to remove bubbles. After that, gradient sintering is performed. First, the temperature is increased from room temperature to 200°C at a rate of 2°C / min and held for 10 min. Then, the temperature is increased to 350°C at a rate of 2°C / min and held for 15 min. Then, the temperature is increased to 500°C at a rate of 2.5°C / min and held for 12 min. After that, the temperature is decreased to 200°C at a rate of 2°C / min and then air-cooled to room temperature. Then, the brushing, degassing and gradient sintering steps are repeated 12 to 14 times. The preprocessing specifically includes: After removing the surface oxide scale by sanding the titanium substrate with 800-grit sandpaper, rinse with deionized water, and then sand with 80-120-grit quartz sand at 3-4 kg / m². The titanium substrate was roughened by sandblasting at a certain pressure to control the surface roughness Ra = 3~5μm. The titanium substrate was then placed in a solution of NaOH with a concentration of 40g / L. Concentration of 40g / L The mixture was kept at 75°C for 25 minutes in a 40 g / L alkaline solution, then removed and washed with deionized water until neutral. The oxalic acid etching process specifically involves immersing the treated titanium substrate in a 12% (w / w) oxalic acid solution at 105°C for 1.5 hours, then rinsing it with deionized water until neutral and drying it at 105°C. When tantalum pentachloride, iridium chlorohydrate, antimony trichloride, cerium nitrate hexahydrate, and iridium tantalum oxide nanocrystal seed crystals are added to the mixed solvent: Weigh out tantalum pentachloride and chloroiridium hexahydrate according to the mass ratio of tantalum to iridium = 6.5:3.5; The total molar amount of antimony trichloride and cerium nitrate hexahydrate is 4% of the total molar amount of tantalum pentachloride and chloroiridium hexahydrate, wherein the molar ratio of antimony trichloride and cerium nitrate hexahydrate is 6:4; The mass of the iridium-tantalum oxide nanocrystal seed crystal is 2% of the total mass of tantalum and iridium elements; The method for preparing the iridium tantalum oxide nanocrystal seed crystal is as follows: Tantalum pentachloride and chloroiridium hexahydrate were weighed according to a molar ratio of 1:1 for tantalum and iridium. The tantalum pentachloride was added to concentrated hydrochloric acid with a mass fraction of 37% under ice bath stirring until dissolved, resulting in a mixed solution with a tantalum ion concentration of 0.2 mol / L. The chloroiridium hexahydrate was added to the mixed solution and stirring was continued until dissolved, resulting in a tantalum-iridium mixed metal salt mother liquor. Anhydrous ethanol was added to the mother liquor of the tantalum-iridium mixed metal salt to adjust the total metal ion concentration in the system to 0.1 mol / L. Then, citric acid monohydrate was added to the system at a molar ratio of citric acid monohydrate to total metal ions = 1.2:1 and stirred until completely dissolved to obtain the first mixed solution. The first mixed solution was placed in a water bath at 40°C, and 10% ammonia solution was added dropwise with stirring to adjust the pH of the system to between 3.0 and 3.
5. After the addition was completed, the mixture was kept warm and stirred for 30 minutes to obtain an iridium-tantalum composite sol. The iridium-tantalum composite sol was aged in a water bath at 60°C for 12 hours to obtain a wet gel. The wet gel was dried at 105°C for 6 hours to obtain an iridium-tantalum dry gel precursor. The iridium-tantalum dry gel precursor was ground into iridium-tantalum dry gel powder with a mesh size of less than 200 mesh. The iridium-tantalum dry gel powder was calcined, heated to 480°C at a rate of 2°C / min, held at that temperature for 1.5 hours, and then cooled to room temperature at a rate of 3°C / min to obtain a preliminary iridium-tantalum composite oxide nanocrystal. The preliminary iridium-tantalum composite oxide nanocrystal was added to anhydrous ethanol at a solid-liquid ratio of 1:10 and ultrasonically dispersed at 200W for 20 minutes. Then, it was centrifuged at 3000r / min for 5 minutes, and the lower precipitate was collected. The lower precipitate was vacuum dried at 60°C to obtain the iridium-tantalum oxide nanocrystal seed crystal.
2. The method for preparing the coated titanium anode material according to claim 1, characterized in that, The mixed solvent comprises the following components by mass fraction: Concentrated hydrochloric acid 12%, n-butanol 65%, and isopropanol 23%; The concentrated hydrochloric acid has a mass fraction of 37 wt%.
3. The method for preparing the coated titanium anode material according to claim 1, characterized in that, The post-processing specifically involves heating to 500°C at a rate of 2°C / min, holding at that temperature for 1 hour, and then allowing the furnace to cool naturally to room temperature.
4. A coated titanium anode material, characterized in that, It is prepared by the method for preparing coated titanium anode material according to any one of claims 1-3.
Citation Information
Patent Citations
A titanium-based iridium tantalum oxide coating anode and a preparation method and application thereof
CN121344574B
Preparation method of low-cost titanium-based coating titanium anode
CN113881978A
Titanium-based anode and preparation method and application thereof
CN114592218A